Association of PNPLA3 rs738409 G/C gene polymorphism with nonalcoholic fatty liver disease in children: a meta-analysis - Shan Tang; Jing Zhang; Ting Ting Mei; Hai Qing Guo; Xin Huan Wei; Wen Yan Zhang; Ya Li Liu; Shan Liang; Zuo Peng Fan; Li Xia Ma; Wei Lin; Yi Rong Liu; et al. (BMC, 2020)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease worldwide. Current studies have shown that PNPLA3 (Patatin-like phospholipase domain containing 3) rs738409 G/C gene polymorphism is associated with adult nonalcoholic fatty liver disease [1, 2].But there is no consensus on the relationship between PNPLA3 rs738409 G/C gene polymorphism and children NAFLD due to differences in population samples. To this end, a meta-analysis of published research is conducted to comprehensively assess the relationship between PNPLA3 gene polymorphism and NAFLD in children. Methods We searched MEDLINE, PubMed, EMBASE, and CENTRAL databases from inception to May 2019. Case-control studies assessing the relationship between PNPLA3 rs738409 G/C gene polymorphism with non-alcoholic fatty liver disease in children were selected according to inclusion and exclusion criteria. Random effects model was used to quantify the association between the PNPLA3 rs738409 G/C gene polymorphism and the susceptibility of children's NAFLD. Fixed effects model was used to quantify the relationship between the PNPLA3 rs738409 G/C gene polymorphism and the severity of NAFLD in children. The Stata 12.0 software was employed for data analysis. Results A total of nine case-control studies were included in this meta-analysis containing data of 1173 children with NAFLD and 1792 healthy controls. Five studies compared NAFLD children and non-NAFLD healthy populations. Statistical analysis showed that PNPLA3 gene polymorphism was significantly associated with children's NAFLD in the allele contrast, dominant, recessive and over dominant models (G vs C,OR = 3.343, 95% CI = 1.524-7.334; GG + GC vs CC,OR = 3.157, 95% CI = 1.446-6.892;GG vs GC + CC,OR = 5.692, 95% CI = 1.941-16.689; GG + CC vs GC,OR = 2.756, 95% CI = 1.729-4.392). Four case-control studies compared Children with nonalcoholic fatty liver (NAFL) and children with nonalcoholic steatohepatitis (NASH). The results showed that the PNPLA3 gene polymorphism was also significantly associated with the severity of NAFLD in children in recessive gene model (GG vs GC + CC,OR = 14.43, 95% CI = 5.985-34.997); The Egger's test revealed no significant publication bias. Conclusions Meta-analysis showed that PNPLA3 gene polymorphism was significantly associated with susceptibility and severity of NAFLD in children.